Identification and biochemical characterization of a novel α-1, 3-mannosyltransferase WfcD from Escherichia coli O141. (18th April 2017) - Chen, Chao; Hou, Xi; Utkina, Natalia; Danilov, Leonid; Zhou, Dawei; Torgov, Vladimir; Veselovsky, Vladimir; Liu, Bin; Feng, Lu
Abstract: Glycosyltransferases (GTs) catalyze the formation of regio- and stereospecific glycosidic linkages between specific sugar donors and recipients. In this study, the function of the wfcD gene from the Escherichia coli O141 O-antigen gene cluster encoding an α-1, 3-mannosyltransferase that catalyzed the formation of the linkage Man(α1-3)-GlcNAc was biochemically characterized. WfcD was expressed in E. coli BL21 (DE3), and the enzymatic product was identified by liquid chromatography-mass spectrometry (LC-MS), collision-induced dissociation electrospray ionization ion trap multiple tandem MS (CID-ESI-IT-MS n ) and glycosidase digestion using the donor substrate GDP-Man and the synthetic acceptor substrate decyl diphosphate 2-acetamido-2-deoxy-α-D-glucopyranose (GlcNAc-PP-De). The kinetic and physiochemical properties and the substrate specificity of WfcD were investigated. WfcD is the first characterized bacterial mannosyltransferase that acts on the Man(α1-3)-GlcNAc linkage. This study enhances our knowledge of the diverse functions of GTs. Graphical abstract: Highlights: We characterized the function of the wfcD gene, part of the Escherichia coli O141 O-antigen gene cluster. The kinetic and physiochemical properties and the substrate specificity of WfcD were investigated. WfcD is the first characterized bacterial mannosyltransferase that acts on the Man(α1-3)-GlcNAc linkage.